(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this research, the behavior of a reinforced concrete chimney was studied under the effect of temperature changes, and a reinforced concrete chimney was designed with a height of 25 meters and modeled by the SAP2000 program. The chimney was exposed to three different temperatures (250°C, 500°C, and 750°C) and the behavior of this chimney was studied and the values were observed without heat and under the effect of each temperature. The values of moments, forces, maximum potentials, and displacements under each temperature were compared. And we take the value of the maximum principal shear Vmax, maximum principal moment Mmax, the maximum principal stress Smax and the displacements U1, U2 and U3. The results showed a significant increase in the value of the moments, stresses, and shears when the temperature increased, and showed the amount of deformation and displacement that occurred with increasing temperatures.